Merger Announcements and Wealth Creation for Shareholders: Evidence from Modern M&As in Indian Public Sector Banks - Maani, Jasmine; A, Dunstan Rajkumar; Barik , Nirakar; Rangaswamy, Easwaramoorthy (International Journal of Accounting and Economics Studies, 2025)
Globalization and liberalization have prompted businesses from developing economies like India to adopt a more proactive approach, opting for mergers and acquisitions (M&A) as a strategy to compete effectively. In recent years, numerous mergers have taken place within the Indian banking sector. This research aims to assess the short-term effect of mergers and acquisitions on returns, employing a comprehensive event study methodology for the period from 2015 to 2020. The market study methodology was utilized to compute abnormal and cumulative abnormal returns, employing both one-factor and two-factor models, to examine how the phenomenon affected share prices before and after the event. Six mergers in Indian Public Sector Banks are analyzed to gauge the effects on shareholder returns following merger announcements. The results indicate mixed observations regarding the impact of mergers and acquisitions on stock price performance. While the majority of firms experienced negative returns, some exhibited positive abnormal and cumulative abnormal returns following these activities. Overall, the market's response to mergers and acquisitions in the Indian banking sector was generally unfavorable. These findings provide valuable insights for investors and management to inform their investment decisions.
Keywords: Merger, Indian Banking Sector, Shareholders' Wealth Effects, Cumulative Abnormal Return, One Factor Model (OFM), Two Factor Model (TFM)